Modified starches or stabilizers in preparation of cheese bread - Letícia Dias dos Anjos (Ciência Rural, 2014)
Cheese bread is a Brazilian product which originated in Minas Gerais and which is highly consumed. In industrial production, there is increasing use of additives which enrich and enhance the physical of this product, adding value in the eyes of the consumer. Thus, the purpose of this paper was to study the effect of addition of modifi ed starch and stabilizers on the physical-chemical of cheese bread. For this reason, measures taken so moisture, pH and acidity, volume, density, coeffi cient of expansion, and compression resistance (texturometer) Results show that the stabilizers used improve these characteristics in the cheese bread, showing better physicochemical characteristics.